2017
DOI: 10.3390/ijgi6030059
|View full text |Cite
|
Sign up to set email alerts
|

Landsat-Based Land Cover Change in the Beijing-Tianjin-Tangshan Urban Agglomeration in 1990, 2000 and 2010

Abstract: Rapid urbanization dramatically changes the local environment. A hybrid classification method is designed and applied to multi-temporal Landsat images and ancillary data to obtain land cover change datasets. A support vector machine (SVM) classifier is used to classify multi-temporal Landsat Enhanced Thematic Mapper Plus (ETM+) images that were collected in 2000 at the pixel level. These images are also segmented with the mean shift method. The impervious surface is refined based on a combination of the segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Among them, the GWR model proposed by Brunsdon et al has been applied in geography and its related disciplines [35]. Wang et al investigated the relationship between land cover and surface temperature in the Beijing-Tianjin-Tanggu urban agglomeration by establishing a GWR model, and the results showed that the land cover ratio and LST were significantly correlated [36]. Kashki et al evaluated the relationship between LST and influencing factors in Shiraz City, Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the GWR model proposed by Brunsdon et al has been applied in geography and its related disciplines [35]. Wang et al investigated the relationship between land cover and surface temperature in the Beijing-Tianjin-Tanggu urban agglomeration by establishing a GWR model, and the results showed that the land cover ratio and LST were significantly correlated [36]. Kashki et al evaluated the relationship between LST and influencing factors in Shiraz City, Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been shown to be accurate for impervious surface mapping, it requires comprehensive reference data, including both land cover labels, and information on change type [2,[24][25][26]. The post-classification analysis classifies each image individually, and information regarding the change is derived based on per-pixel comparison [27,28], nevertheless, the limited availability of multi-temporal retrospective reference data has been a challenge [29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not separated in use and the term broadly used among remote sensing scientists. LULC changes represents result of human activity influence on surrounding area [3][4][5][6][7]. Multi-spectral data is widely used among RS researchers to detect and learn timely temporal changes of human-environment interaction as well as natural disaster on land use [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%